2009
DOI: 10.1002/adem.200900110
|View full text |Cite
|
Sign up to set email alerts
|

Superplastic Behavior in MgZnY Alloy with Dispersed Quasicrystal Phase Particles

Abstract: An MgZnY alloy with a dispersion of quasicrystal phase particles showed low‐temperature superplastic behavior, and the dominant deformation process was grain boundary sliding. Observations of the deformed microstructure showed that the quasicrystal phase particles were an obstacle to dislocation movements; the kinetics of the superplastic behavior were lower than those of a conventional magnesium alloy. This alloy also demonstrated a high possibility for secondary forming – i.e., superplastic forging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…Figure shows variation of flow stress at a true strain of 0.2 as a function of strain rate at different temperatures. The m values vary from 0.35 to 0.53, indicating that the superplastic mechanism could be a combination of dislocation viscous glide and GBS . The maximum elongation of 512% is achieved at 523 K with initial strain rate of 5 × 10 −4 s −1 , corresponding to the maximum m ‐value of 0.53, which implies that GBS becomes the predominant mechanism of deformation.…”
Section: Resultsmentioning
confidence: 98%
“…Figure shows variation of flow stress at a true strain of 0.2 as a function of strain rate at different temperatures. The m values vary from 0.35 to 0.53, indicating that the superplastic mechanism could be a combination of dislocation viscous glide and GBS . The maximum elongation of 512% is achieved at 523 K with initial strain rate of 5 × 10 −4 s −1 , corresponding to the maximum m ‐value of 0.53, which implies that GBS becomes the predominant mechanism of deformation.…”
Section: Resultsmentioning
confidence: 98%
“…5 of Ref. [37]. This means that not only basal slips but also nonbasal slips are activated during slip accommodation.…”
Section: Texture and Tensile Ductility At Room Temperature Of Rod Andmentioning
confidence: 92%
“…5b) may reflect a slow grain rotation associated with this mechanism. Recently, Somekawa et al [37] suggested a slip system for slip accommodation in a particle-dispersed superplastic Mg-Zn-Y alloy rod. They observed two types of dislocation activity in a grain: a basal slip around particles and a nonbasal slip at the lower left area in Fig.…”
Section: Texture and Tensile Ductility At Room Temperature Of Rod Andmentioning
confidence: 99%
“…23) A previous study also confirmed that grain boundary sliding is the dominant deformation mechanism at the temperature of 573 K using the MgZnY alloy with a grain size of less than 10 µm. 25) On the other hand, the quasicrystal phase has the role of creating the pinning effect during the deformation at not only room temperature 11) but also at even elevated temperatures, i.e., superplastic regime. 25) However, these previous fracture surface observations show that the quasicrystal phase is not the origins of the crack propagation site in the fatigue tests 26) and the micro-void nucleation site in the toughness tests 11) due to the strong matching between the quasicrystal phase and the matrix.…”
Section: Resultsmentioning
confidence: 99%